셀룰러 망 통신보안을 위한 D2D 통신 송신전력 제어 기법 - 이기송(Kisong Lee); 홍준표(Jun-Pyo Hong) (한국정보통신학회논문지, 2017)
In this paper, we propose a power control technique for D2D communication in the heterogenous network consisting of cellular and D2D communication systems. Although the transmit signal of D2D communication degrades the performance of cellular system by interfering the signal reception at CU in the conventional heterogenous networks without eavesdroppers, it can be utilized as jamming signal for preventing other devices from recovering the transmitted information if there are eavesdroppers in the network. The proposed power control technique maximizes the achievable rate of D2D communication while ensuring the target security performance of cellular communication system. Through simulation results, we validate the analysis results and compare the performance with the conventional D2D communication scheme that utilizes its full transmit power for maximizing the achievable rate regardless of the performance of cellular system. 본 논문에서는 셀룰러 통신과 D2D (device-to-device)통신이 같은 주파수를 통해 이루어지는 이기종 네트워크(heterogenous network)에서 셀룰러 망의 보안통신을 돕기 위한 D2D 통신 디바이스의 전력제어 기법을 제안하고 성능을 살펴본다. 기존의 보안통신이 고려되지 않은 이기종 네트워크에서는 D2D통신 신호가 간섭으로 작용하여 셀룰러 통신 성능에 악영향을 미쳤으나 도청자를 고려한 보안통신에서는 D2D통신 신호가 도청자의 신호수신을 방해하여 보안 전송률 성능 향상에 도움이 될 수 있다. 본 연구에서는 셀룰러 망의 보안통신 요구치를 만족시키며 D2D 통신 전송률을 극대화 시킬 수 있는 새로운 전력제어 기법을 제안하고 최적화 문제를 통해 최적 송신 전력의 closed-form 표현을 도출하였다. 또한 시뮬레이션을 통해 제안기법의 성능 특성을 확인하였다.